Perlindungan Hukum Terhadap Perempuan Korban Tindak Pidana Dalam Perundangan Indonesia - Atmaja, Iin Suny; Alviah, Alviah (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2023)
The position of women in civil cases in Indonesia still requires more attention so that they are equal in the eyes of law and legislation. In order to support this statement, this research is specifically aimed at inventorying criminal law in Indonesia. So the literature review in the form of legal inventory has primary data from rules and regulations related to criminal cases, especially the Criminal Code. One important conclusion is the importance of imposing fines and compensation on women victims of criminal acts in legislation.